Effects of different levels of dietary glucosamine on some growth performance, serum immune and biochemical indices of Siberian sturgeon (Acipenser baerii) - Maryam Nazari; Seyed Pezhman Hosseini Shekarabi; Mehdi Shamsaie Mehrgan (University of Guilan, 2020)
This study was performed to evaluate the effects of different dietary levels of glucosamine on growth performance, serum biochemical and immune indices of Siberian sturgeon. Fish (9.3 ± 0.4 g initial weight) in 12 fiberglass tanks with a density of 15 fish/tank were randomly distributed and fed with different levels of glucosamine including: 0 (control), 250, 750 and 1500 mg per kg of diet (C0, T250, T750 and T1500, respectively) for 56 days. Based on the results, the highest final weight (63.1 ± 1.6 g), weight gain (54.14 ± 1.82 g), body weight increase (558.28 ± 23.23%), and specific growth rate (3.36 ± 0.08%/day) were observed in T1500 compared to the other treatments (p < 0.05). The results of this study showed that there are no significant differences in survival rate and blood glucose levels among the experimental treatments (p>0.05). The results of the serum immune indices exhibited that the highest levels of IgM (38.1 ± 0.5 mg/dL), C3 (5.20 ± 0.17 mg/dL) and C4 (20.72 ± 1.0 mg/dL) were observed in T1500 compared to other experimental treatments (p < 0.05). On the other hand, by increasing glucosamine concentration, the activity of hepatic enzymes including aspartate aminotransferase, alanine aminotransferase, and alkaline phosphatase was decreased and the lowest levels were observed in T1500 (p < 0.05). In conclusion, glucosamine, especially at the level of 1500 mg/kg of diet, displayed positive effects on the growth and immune indices of juvenile Siberian sturgeon.